2008
DOI: 10.2334/josnusd.50.481
|View full text |Cite
|
Sign up to set email alerts
|

Changes in elastic modulus of adhesive and adhesive-infiltrated dentin during storage in water

Abstract: The purpose of this study was to determine the elastic modulus of components at the resin-dentin interface with the use of an ultrasound device. Dentin slabs were obtained from freshly extracted bovine incisors shaped into a rectangular form. After demineralization, the dentin specimens were immersed in adhesives and polymerized. Adhesives were also polymerized and trimmed into the same shape as the dentin slabs. The specimens were then immersed in distilled water at 37°C for up to one year. The ultrasound equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
0
15
0
12
Order By: Relevance
“…20 Further, exposure of root dentin to EDTA for extended periods may decrease the modulus of elasticity and the flexure strength of dentin. 21 Such decrease may adversely affect the physical and mechanical properties of dentin, and eventually increase the risk for root fracture. 22 Hence, the use of alternative chelating solutions with less or no detrimental effect on root dentin would be most desirable.…”
Section: Discussionmentioning
confidence: 99%
“…20 Further, exposure of root dentin to EDTA for extended periods may decrease the modulus of elasticity and the flexure strength of dentin. 21 Such decrease may adversely affect the physical and mechanical properties of dentin, and eventually increase the risk for root fracture. 22 Hence, the use of alternative chelating solutions with less or no detrimental effect on root dentin would be most desirable.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term use of these agents at high concentrations can cause undesired effects on the root canal walls, such as significantly reduced flexural strength, microhardness, root canal dentin roughness, and elastic modulus (26)(27)(28). Çalt and Serper (16) reported that a 10-min application of 17% EDTA as an irrigation agent caused peri-and intratubular dentinal erosion.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura sugere a realização de ensaios de nanodureza em áreas restritas e estreitas como a interface adesiva a fim de evidenciar a dureza das camadas que compõem esta interface, como a camada de adesivo e a camada híbrida (Hosoya et al, 2007;Yasuda et al, 2008;Pongprueksa et al, 2008 (Leitune et al, 2013a). Outro estudo deste grupo testou a incorporação de niobium pentoxide a um adesivo experimental e ao avaliar a microdureza, grau de conversão, radiopacidade e a caracterização da interface adesiva com micro-Raman, concluíram que o composto inserido pode ser usado como uma alternativa na composição de adesivos resinosos (Leitune et al, 2013b).…”
Section: Discussionunclassified
“…Suas dimensões reduzidas permitem a obtenção das propriedades mecânicas de uma região específica do material (Fujisawa;, podendo ser utilizado em qualquer superfície sólida incluindo materiais poliméricos e biológicos (Schuh, 2006;Mencík et al, 2009 (Hosoya et al, 2007;Yasuda et al, 2008;Pongprueksa et al, 2008;Bengtson, 2010). Diversas são as variáveis testadas com a finalidade de otimizar as propriedades mecânicas da interface de união como por exemplo, o modo passivo ou ativo de aplicação dos sistemas adesivos (Higashi et al, 2009;Pupo et al, 2012), a umidade dentinária mantida previamente à hibridização (Higashi et al, 2009), os diversos sistemas adesivos utilizados (Hosoya et al, 2008;Pongprueksa et al, 2008) assim como diferentes substratos e profundidades dentinárias (Pupo et al, 2012).…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation